The immediate psychological response of the general population in Saudi Arabia during COVID-19 pandemic: A cross-sectional study. Issue 2 (February 2021) - Joseph, Royes; Lucca, Jisha M.; Alshayban, Dhfer; Alshehry, Yasir A.
Abstract: Background: The outbreak of COVID-19 may differentially exacerbate anxiety and stress in people subjected to the real or perceived threat of the virus. Method: An online cross-sectional survey was carried out to assess the general population's psychological response during the initial state of the outbreak in Saudi Arabia. The study used brief screening tools PHQ-4 for anxiety-depression symptoms and IES-6 for posttraumatic stress disorder symptoms. Results: Among the 584 respondents, 19.8% and 22.0% reported moderate to severe anxiety and depression symptoms respectively. According to the combined PHQ-4 score, 14.5% of participants showed moderate to severe anxiety or depression disorder. Overall, 64.8% met the level of clinical concern for posttraumatic stress disorder and 51.3% met the level of probable posttraumatic stress disorder diagnosis. Multivariate analyses showed that females, non-Saudi nationalities, and those who had a history of mental illness were more vulnerable to anxiety and depression disorders than their counterparts, whereas a higher prevalence of distress symptoms was reported among those who prefer Arabic over English for communication. It was found that people whose colleagues or family infected with the disease were more likely to report moderate to severe symptoms of anxiety or depression and distress. The study further showed that the higher the perceived threat, the higher the chances of exhibiting anxiety-depressive disorder symptoms and distress symptoms. Conclusion: The findings might be a matter for serious concern, and considerable attention is required from authorities and policymakers regarding early detection and treatment of these illnesses in order to reduce the burden of the pandemic related mental illness.